False killer whales (Pseudorca crassidens Cetacea: Delphinidae) along the Pacific coast of Central America and Mexico: Long-term movements, association patterns and assessment of fishery interactions - Douglas, Annie B. (2023)
Introduction: Worldwide, false killer whales (Pseudorca crassidens) are infrequently encountered, yet long-term studies have shown strong site fidelity as well as long-term associations among individuals in several locations. Detailed studies of this species have primarily been conducted around tropical oceanic islands or in the subtropical southern hemisphere. Objectives: We assess movements and association patterns among false killer whales along the Pacific coasts of the USA, Mexico, Guatemala, Nicaragua, Costa Rica including Isla del Coco, and Panama, representing one of the longest-running (albeit non-continuous) studies of this species. We also examine photos for evidence of interactions with fisheries, a known source of mortality to false killer whales. Methods: From Central America, we selected 212 individuals (50 encounter groups) out of 244 individuals (56 encounters) for inclusion in analyses based on photo quality and distinctiveness. Photos were collected on dedicated surveys from 1991-1994 and dedicated and opportunistic surveys from 1998-2022. Other than the effort off the oceanic Isla del Coco (1993-1994), surveys were undertaken in continental shelf waters. Additionally, we selected by photo quality and distinctiveness 124 (33 encounter groups) out of 189 individuals from southern California and Mexico for inclusion in these analyses. Association patterns were analyzed in SOCPROG and movements were analyzed in R. Results: Of the 328 total individuals, 158 (48.2 %) were encountered more than once, and 114 (34.8 %) were re-sighted after a year or more. The longest individual sighting history spanned 26.2 years with six re-sightings over that period between southern Costa Rica and Panama. Association and movement analyses revealed that individuals identified off southern Costa Rica and Panama linked into a single social network, with extensive movements between the two countries. Three individuals encountered off northern Costa Rica were re-sighted off northern Nicaragua, and individuals encountered off Nicaragua were encountered off Guatemala and central mainland Mexico. Nine matches were found among false killer whales between central mainland Mexico and Central America. There were no matches between the mainland coastal waters and the 33 individuals encountered around Isla del Coco. Dorsal fin disfigurements consistent with interactions with line fisheries ranged from 0 to 21 % for individuals within social clusters identified by community division. Conclusions: The infrequency of sightings combined with a high re-sighting rate of individuals and groups from the same area, suggests multiple small populations with large home ranges that include coastal waters. Small populations are sensitive to environmental changes, and as the human population grows, so do the demands on fisheries and ecotourism, which could directly impact the different populations. Additional effort in offshore areas is needed to determine the population status of false killer whales in pelagic waters, how often false killer whales using coastal waters move into pelagic waters, and the relationship between whales in the two habitats.